Pastoral Counseling, Supervision/Consultation, Burnout, and Ethical Violations: A Review of the Literature - Brand, Sandra; Tadros, Eman (KMAN Counseling & Psychology Nexus, 2025)
Existing research has demonstrated that the experience of stress and burnout has the potential to negatively impact the cognitive processes involved in decision-making. Consequently, this may result in a heightened susceptibility for counselors to engage in unethical decision-making.  Research exists about counselors, social workers, psychologists, and clergy who experience burnout. Research revealed consistent topics about leadership roles, supervision/consultation, and how entitlement can be the most problematic issue for anyone in a leadership position. Much of the literature indicated that burnout is prevalent among clergy and recommends having some support.